A Comprehensive Case Study of a Frontal Mineral Dust Storm in spring over Iraq - O. Roomi, Thaer; N. Zeki, Khawla; F. Hassoon, Ahmed (Iraqi Journal of Science, 2021)
Dust storms are among the most important weather phenomena in Middle East. The Shamal dust storms are dominated across Iraq and the whole Middle East, especially in summer. However, frontal type of dust storms is possible in winter and spring. In this research, a comprehensive case study was conducted to a dust storm that occurred on 20 March 2016 from many perspectives: synoptic, satellite imagery, dust concentration analysis, visibility reduction, and aerosol optical depth. The study shows that the dust storm initiated inside Syria and moved eastward with the movement of the front. Dust concentrations and aerosol optical depth were also discussed that simulate the dust storm over Iraq in a reasonable way with some differences. The dust concentrations values increase gradually during the early hours of 20 March at 1200 UTC to become within (200-5000) . The dust concentrations comparison with some surrounding countries shows that Iraq had the maximum value at the dust storm time. An experimental relationship to calculate the dust concentration from visibility was tested according to the multi-model products and revealed acceptable estimates. Dust aerosol optical depth offers good means to quantify the dust amount in the Middle East where the dust is the determining factor. Additional investigation was done by using the relative vorticity and the potential vorticity. The results of this investigation show that there are upper shortwaves that are responsible of strengthening of the low pressure system at the surface. The computed value of potential vorticity advection was estimated to be about (2.7×10-4 K m2/kg s) along a distance of about 500 km which suggested a high value of divergence east of the system which lead to a significant updraft.